Digital Smart Classroom Integration: Enhancing Student Learning Motivation and Pedagogical Dynamics - Riza Kurnia; Saipul Annur; Afriantoni Afriantoni; Yuniar Yuniar (Journal of General Education and Humanities, 2026)
This study evaluates the implementation of the Digital Smart Classroom program at MAN 3 Palembang using the CIPP (Context, Input, Process, Product) evaluation model. The research is driven by the disparity between rapid technological infrastructure expansion and educators' actual pedagogical readiness. Employing a qualitative-dominant mixed-methods approach, data were gathered through in-depth interviews with 18 key informants, participatory observations, and questionnaires distributed to 72 respondents. The findings reveal that while the Context and Input phases show strong institutional alignment and infrastructure readiness (score 3.70–3.90), teacher digital pedagogical competence remains a critical bottleneck (score 3.60). Process evaluation indicates that digital transformation has successfully fostered an active learning environment (score 4.05), although it is frequently hindered by network stability issues (score 3.45). Ultimately, the Product evaluation demonstrates that the program significantly enhances student motivation and satisfaction, placing it in the "Very Good" category (score 4.21). The study concludes that successful digital transformation in madrasahs necessitates a strategic shift from hardware-oriented procurement to sustainable human resource development, with a focus on innovative digital pedagogical strategies.